Comparison of pain and discomfort in supine and lateral positions after surgery for lumbar degenerative disease: A prospective randomized controlled study. (November 2022) - Aoki, Yasuchika; Suzuki, Makoto; Takahashi, Hiroshi; Nakajima, Arata; Sonobe, Masato; Kotani, Toshiaki; Nakajima, Takayuki; Sato, Yusuke; Inoue, Masahiro; Saito, Junya; Norimoto, Masaki; Eguchi, Yawara; et al.
Abstract: Introduction: To compare postoperative pain and discomfort between supine and lateral positions after lumbar surgery, a prospective randomized controlled study was performed. Methods: Forty-three patients with lumbar degenerative disease, treated by decompression (n = 23) or fusion surgery (n = 20), were randomly assigned to be placed in either the supine (supine group: n = 21) or lateral (lateral group: n = 22) position postoperatively, and asked to maintain their position until a day after the surgery. Postoperative back pain and discomfort (visual analog scale [VAS], 0–100 mm) and the number of patients who could maintain their position were examined. Results: The VAS scores for back pain (supine : 64.9 ± 22.0, lateral: 55.7 ± 21.4) showed no significant difference between the positions. However, the supine group showed significantly more severe discomfort (75.6 ± 15.7) than the lateral group (64.9 ± 15.7, p = 0.039). Significantly fewer patients maintained their position in the supine group (28.2%) than in the lateral group (68.2%; p = 0.022). Among patients who underwent fusion surgery, significantly fewer patients maintained their position in the supine group (10.0%) than those in the lateral group (60.0%, p = 0.029). Conclusion: Postoperative discomfort was significantly reduced in the lateral position than in the supine position; thus, the lateral position is more suitable after lumbar surgery in terms of postoperative discomfort.